Strategi Pemasaran Berbasis Konsep Alam Terbuka Dalam Meningkatkan Daya Tarik Dan Nilai Daya Saing Konsumen Pada Warung Senyum Sawahan Banyuwangi - Nazwa Nazulla Billuna; Aliya Ramadhani; Nanik Sulistiyowati; Elok Rosyidah (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study examines an open-nature-based marketing strategy in enhancing consumer attraction and competitive value at Warung Senyum Sawahan Banyuwangi. The main issue addressed is the intense competition among culinary UMKM, which requires innovative marketing strategies focusing on consumer experience. The objective of this research is to identify and describe the implementation of an open-nature-based marketing strategy and its impact on consumer attraction and competitiveness. This study employs a descriptive qualitative method with a case study approach. Data were collected through observation, in-depth interviews, and documentation involving the owner, employees, and customers of Warung Senyum Sawahan. The findings indicate that the integration of an open-natural atmosphere, rice field scenery, affordable pricing, and consistent product and service quality significantly enhances consumer attraction and competitive advantage. Moreover, the positive emotional experience perceived by customers encourages loyalty and word-of-mouth promotion, strengthening Warung Senyum Sawahan’s position as a nature-based culinary destination in Banyuwangi.